Raziskovanje odnosov etničnosti in manjšin v Sloveniji - Šumi, Irena (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
RESEARCHING ETHNICITY AND MINORITIES IN SLOVENIA: TOWARDS A REORGANISED PERSPECTIVE. Although the Institute for Ethnic studies after eight decades of its existence and work still fights, somewhat anachronistically, various extra-scientific usurpations of its field of investigations, the contributions to the second panel of the jubilee conference in 2005 show that Slovenian ethnic studies encompass as substantial professional circle that goes beyond the associates of the Institute itself, but for whom the Institute was decisively formative. The six contributions from, in order of appearance: IR specialist Hannah Starman; sociologist Marija Jurić Pahor; anthropologist Duška Knežević Hočevar; geographer and demographer Damir Josipovič, and anthropologists Alenka Janko Spreizer and Gregor Starc, are bound by a joint thematic thread: from theoretisations of (national) memory to ideologies of nationalism and autochtonism to theoretisations of manifest nationalism which, again, uses collective memory as a key concept.
Keywords: Slovenia; Slovenija; narodno vprašanje; narodne manjšine; etničnost; nacionalizem; nationalism; raziskave; znanstvenoraziskovalno delo